2017
DOI: 10.3390/ijms18030535
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Methylated Loci Persisting from Sessile Serrated Polyps to Serrated Cancers

Abstract: Although serrated polyps were historically considered to pose little risk, it is now understood that progression down the serrated pathway could account for as many as 15%–35% of colorectal cancers. The sessile serrated adenoma/polyp (SSA/P) is the most prevalent pre-invasive serrated lesion. Our objective was to identify the CpG loci that are persistently hyper-methylated during serrated carcinogenesis, from the early SSA/P lesion through the later cancer phases of neoplasia development. We queried the loci h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
(72 reference statements)
3
9
1
1
Order By: Relevance
“…Several of the observed targets of differential methylation, for example, AXIN2, DKK3, GRIA4, MLH1, SEPT9, SFRP1, SLC8A1, and SYN3, were also reported in recent studies. 21,42,43 Additionally, our study confirmed earlier publications that DMPs are not randomly distributed within the genome 13,22,34 : DMPs in CGIs were frequently hypermethylated while open sea and shelf regions were hypomethylated;…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Several of the observed targets of differential methylation, for example, AXIN2, DKK3, GRIA4, MLH1, SEPT9, SFRP1, SLC8A1, and SYN3, were also reported in recent studies. 21,42,43 Additionally, our study confirmed earlier publications that DMPs are not randomly distributed within the genome 13,22,34 : DMPs in CGIs were frequently hypermethylated while open sea and shelf regions were hypomethylated;…”
Section: Discussionsupporting
confidence: 90%
“…B, Quantitative GREM2 gene body methylation analysis of four CpG dinucleotides (FOR-assay) in primary adenomas with and without recurrence, and recurrent adenomas. Additionally, our study confirmed earlier publications that DMPs are not randomly distributed within the genome13,22,34 : DMPs in CGIs were frequently hypermethylated while open sea and shelf regions were hypomethylated; C, Quantitative GREM2 gene body methylation analysis of four CpG dinucleotides (REV-assay) in primary adenomas with and without recurrence and recurrent adenomas.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…We also observed that methylation increased in this region following MBC2, which may indicate that a healthier lifestyle downregulates the protein in immune cells. In contrast, a small study by Andrew et al found that ZNF568, a zinc finger transcription factor, was hypermethylated in sessile serrated colon polyps (n = 34) compared to normal adjacent mucosal tissue (n = 15) [48]. We also observed an increase in ZNF568 methylation following improved health behaviors at only 9 months.…”
Section: Discussioncontrasting
confidence: 88%
“…GSG1L was inactive in the AMPA-type glutamate receptors (AMPARs) in cancer (Gu et al, 2016;Andrew et al, 2017). In addition, GBM could secrete glutamate and trigger the AMPARs, leading to cell death in neurons surrounding the tumor (Van Vuurden et al, 2009).…”
Section: Discussionmentioning
confidence: 99%